2018
DOI: 10.3390/agriculture8100158
|View full text |Cite
|
Sign up to set email alerts
|

Sorption to Biochar Impacts β-Glucosidase and Phosphatase Enzyme Activities

Abstract: Extracellular enzymes catalyze biogeochemical reactions in soil, cycling carbon and nutrients in agricultural systems. Enzymes respond quickly to soil management, including organic amendment inputs, such as biochar, a charcoal-like solid byproduct of bioenergy production. In a previous agricultural field trial, a pine biochar amendment caused an approximately 40% decrease in the enzyme activities of β-glucosidase (BG) and phosphatase (PHOS). The large surface area of the pine biochar has the potential to sorb … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(27 citation statements)
references
References 38 publications
1
22
0
Order By: Relevance
“…This is consistent with previous results [15]. Interestingly, biochars prepared at 400 • C led to a larger decrease in β-glucosidase compared to those prepared at 300 • C and 500 • C. Inherent differences in the biochars, for example, hydrophobicity, surface area and pore size, could also be involved in this effect [20,21], although these mechanisms are poorly understood.…”
Section: Resultssupporting
confidence: 91%
“…This is consistent with previous results [15]. Interestingly, biochars prepared at 400 • C led to a larger decrease in β-glucosidase compared to those prepared at 300 • C and 500 • C. Inherent differences in the biochars, for example, hydrophobicity, surface area and pore size, could also be involved in this effect [20,21], although these mechanisms are poorly understood.…”
Section: Resultssupporting
confidence: 91%
“…However, in a number of experiments, the mechanisms behind the biochar effect on phosphatases has not been clarified, even though biochar can increase the soil pH. Li et al (2017) observed that biochar addition enhanced alkaline phosphatase activity [29][30][31]. Masto et al (2013) reported that biochar increased acid phosphatase activity by 32% and alkaline phosphatase activity by 22.8% [12].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the high surface area and porous nature of biochar allows for chemi-and physi-sorption of N compounds, respectively [3,12]. Further, biochar may also limit mineralization of organic matter through suppression of enzymatic activity via direct sorption of enzymes to the biochar surface [15], which could also contribute to lower mineral N availability through reduced breakdown of nitrogenous compounds. Notably, biochar-induced SIN reductions have been shown to be associated with reduced crop yield [16], and thus biochar-induced increases in N fixation during the alfalfa phase of a crop rotation may provide an alternative N source to support overall productivity.…”
Section: Introductionmentioning
confidence: 99%
“…Ecological tools can be used to directly quantify nutrient fluxes or to gain broader characterizations of the biological system. The difference in 15 N natural abundance between a non-fixing reference plant and an N-fixing legume can indicate relative differences in N fixation between treatments and over time, as well as transfer of fixed N from the N-fixing plant to the reference plant [35,36]. Since it is challenging to measure N fixation directly, it is important to employ multiple lines of evidence to measure changes in N fixation [37].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation